FAKTOR-FAKTOR YANG MEMENGARUHI HARGA SAHAM PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESA - Suyanto, Suyanto; Nursanti, Ati (Jurnal Neraca: Jurnal Pendidikan dan Ilmu Ekonomi Akuntansi, 2017)
AbstractBefore performing stock investment, individual or company must ensure that the investment is appropriate. This can be done by applying a variety of alternative ways of assessing whether the selected stock is really a stock that will provide benefits in the future. One alternative is a fundamental analysis of investment appraisal or performance of the company. Return On Asset, Debt to Total Asset and Net Profit Margin is a ratio that shows the companyâs ability to generate profit and the ratio that measures total corporate debt financed by the assets of the company, which is one way to find out the performance of the company.This research is purposed to determine the influence of Return On Asset, Debt to Total Asset and Net Profit Margin towards Stock Prices. The population in this reaserch are Go Public companies, Food and Beverage Sector, which listed in Indonesian Stock Exchange during 2010-2015 period. Sample selection technique in this research is purposive sampling. Nine companie have been acquired that meet the research sample criteria. This research use secondary data who analyzed with descriptive method and multiple linier regression who tested with experiment classic assumption. The result of research point out indeed Return On Asset, Debt to Total Asset, and Net Profit Margin according to simultaneous influential significant toward dependence variabel is stock prices. According to partial Return On Asset and Debt to Total Asset in not influential significant toward stock prices to Food and Beverage business who listed in Indonesian Stock Exchange period 2010-2015. Meanwhile Net Profit Margin have influence significant toward stock prices to Food and Beverage business who listed in Indonesian Stock Exchange period 2010-2015.Keyword : Return On Asset, Debt to Total Asset, Net Profit Margin, Stock Prices